2023
DOI: 10.1002/iid3.858
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of the BBIBP‐CorV vaccine in patients with autoimmune inflammatory rheumatic diseases undergoing immunosuppressive therapy in a monocentric cohort

Abstract: Introduction Vaccination plays a fundamental role in mastering the COVID‐19 pandemic and protecting vulnerable groups. Persons with autoimmune inflammatory rheumatic diseases (AIIRD) requiring immunosuppressive therapies are prioritized for vaccination. However, data concerning immunogenicity and safety of the BBIBP‐CorV vaccine in immunosuppressed patients are not found. This study presents data on the efficacy and safety of the BBIBP‐CorV vaccine in immunosuppressed patients compared to healthy controls. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(93 reference statements)
2
3
0
Order By: Relevance
“…Previous SARS-CoV-2 infection revealed to be one of the main factors associated with increased immunogenicity to COVID-19 vaccine in our population, in line with data reported in literature [23,31,34,37]. A study by Saleem et al involving 100 patients with RA reported lower seroconversion rates (55.4%) in patients without previous COVID-19 than in those previously infected (100%) [31].…”
Section: Discussionsupporting
confidence: 91%
“…Previous SARS-CoV-2 infection revealed to be one of the main factors associated with increased immunogenicity to COVID-19 vaccine in our population, in line with data reported in literature [23,31,34,37]. A study by Saleem et al involving 100 patients with RA reported lower seroconversion rates (55.4%) in patients without previous COVID-19 than in those previously infected (100%) [31].…”
Section: Discussionsupporting
confidence: 91%
“…Previous SARS-CoV-2 infection was revealed to be one of the main factors associated with increased immunogenicity to COVID-19 vaccine in our population, in line with the data reported in the literature [ 23 , 31 , 34 , 37 ]. A study by Saleem et al involving 100 patients with RA reported lower seroconversion rates (55.4%) in patients without previous COVID-19 than in those previously infected (100%) [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“… 36 These findings are consistent with other studies indicating the immunogenicity of COVID-19 vaccines against SARS-CoV-2 in these patients. 9 , 37 It is reported that immunization with SARS-CoV-2 mRNA and inactivated CoronaVac vaccines provided a suitable titer of neutralizing antibody in the majority of patients with autoimmune diseases, however, the patients had a reduction in antibody response compared to the healthy individuals. 9 , 38 , 39 These observations propose that the reduction in production of SARS-CoV-2 neutralizing antibodies may correlate to the undesirable effects of immunosuppressive treatments on the immunogenicity of COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with some reports showing the first dose of mRNA vaccine produced antibody responses in seropositive subjects, which were sometimes exceeded titers observed in seronegative subjects received two doses of the mRNA vaccines. 9 , 49 It is shown that the BNT162b2 SARS‐CoV‐2 vaccine had the ability to induce IgG level in both seropositive and seronegative individuals; however, only individuals with pre‐existing immunity showed the increased levels of IgM and IgA after primary vaccination. In line with the impacts of the Oxford-AstraZeneca, subjects already contracted SARS-CoV-2 produced neutralizing antibodies against alpha, D614 G, beta, delta, and gamma variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation